Physical modeling for the evaluation of the seismic behavior of square tunnels - Tsinidis, Grigorios; Heron, Charles; Pitilakis, Kyriazis; Madabhushi, Gopal (Springer, 2014)
The Chapter summarizes results from dynamic centrifuge tests performed on a rectangular tunnel model embedded in dry sand. The tests were carried out at the geotechnical centrifuge facility of the University of Cambridge, within the Transnational Access Task of the SERIES Research Project (Project: TUNNELSEIS). The experimental data is presented in terms of acceleration and displacement-time histories in the soil and on the tunnel, soil surface settlements, earth pressures on the side walls of the tunnel and internal forces of the tunnel lining. The goal of the experiment is twofold: to better understand the seismic behavior of these types of structures, and to use the high quality and perfectly constrained data to validate the numerical models which are commonly used for the design of rectangular embedded structures. The interpretation of the results reveals (i) rocking response of the tunnel model, (ii) existence of residual values on the earth pressures on the side walls and on the internal forces and (iii) important influence of the tunnel on the shear wave field. These issues are not well understood and are usually not taken into account in the simplified seismic analysis methods.